DIFFERENCES IN LOW BACK PAIN PAIN LEVEL IN PATIENTS USING THE LUMBAL CORSET AND NON USING THE LUMBAL CORSET - Susanti, Susanti; Bistara, Difran Nobel (Jurnal Keperawatan Respati Yogyakarta, 2021)
Pain is a problem that is often encountered in everyday life and is a common reason people seek health care. More than half of all respondents have low back pain problems. This can cause pain and reduce the ability to move, which can prevent you from performing daily activities. The most common factor influencing the occurrence of low back pain is age. Efforts that must be made by health workers are to provide education about the use of a lumbar corset to reduce pain in patients with low back pain or prevent the recurrence of back pain in people who have a history of low back pain. The purpose of this study was to determine the difference in pain levels in respondents with low back pain respondents who used a lumbar corset and did not use a lumbar corset at the Ketabang Health Center. The design of this study was non-experimental with the mann-whitney comparison method. The sampling technique used total random sampling. The population in this study were respondents with low back pain who wore a lumbar corset and did not wear a lumbar corset, each of 20 respondents. Data collection using a questionnaire sheet Modified Oswestry Low back pain Disability Questionnaire. Statistical tests using SPSS showed that p = 0.028 (Î± = 0.05) where H0 was rejected and H1 was accepted, meaning that there was a difference between the level of pain in respondents with low back pain who wore a lumbar girdle and did not wear a lumbar girdle. This shows that the use of a lumbar corset or assistive device in the treatment of low back pain is very effective in reducing pain in respondents with low back pain. Respondents are expected to be able to live a healthy lifestyle and wear a lumbar corset to reduce pain. Keywords: Low Back Pain; Pain; Lumbar Corset